2019
DOI: 10.1002/iub.2113
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin attenuates alcoholic fatty liver through regulation of lipin‐1 signaling

Abstract: Alcoholic liver disease (ALD) is generated from excessive alcohol consumption, characterized by hepatic steatosis. Mechanistically, excessive hepatic lipid accumulation was attributed to the aberrant lipin-1 signaling during the development of alcoholic steatosis in rodent species and human. Dihydroartemisinin (DHA) has been recently identified to relieve hepatocytes necrosis and prevent from hepatic steatosis in alcohol-induced liver diseases; however, the role of DHA in ALD has not been elucidated completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Lipin-1 is further divided into two protein subtypes in liver tissue, lipin-1α and lipin-1β. Lipin-1α is primarily distributed in the nucleus of hepatocytes and promotes the expression of fatty acid oxidation genes, whereas lipin-1β is primarily distributed in the cytoplasm and promotes the expression of fatty acid synthesis genes ( Hu et al, 2013 ; Chen et al, 2019b ). Chen et al investigated whether dihydroartemisinin alleviated AFLD by regulating lipin-1 signaling pathway ( Chen et al, 2019b ).…”
Section: The Role Of Amp-activated Protein Kinase-mediated Signal Axe...mentioning
confidence: 99%
“…Lipin-1 is further divided into two protein subtypes in liver tissue, lipin-1α and lipin-1β. Lipin-1α is primarily distributed in the nucleus of hepatocytes and promotes the expression of fatty acid oxidation genes, whereas lipin-1β is primarily distributed in the cytoplasm and promotes the expression of fatty acid synthesis genes ( Hu et al, 2013 ; Chen et al, 2019b ). Chen et al investigated whether dihydroartemisinin alleviated AFLD by regulating lipin-1 signaling pathway ( Chen et al, 2019b ).…”
Section: The Role Of Amp-activated Protein Kinase-mediated Signal Axe...mentioning
confidence: 99%
“…DHA attenuated alcohol-induced lipid accumulation in mouse livers by suppressing stearoyl-CoA-desaturase 1 (SCD1), Fas, and SREBP-1c, while increasing the expression of PPAR-α and carnitine palmitoyltransferase 1A (CPT-1A), the regulator of fatty acid oxidation [ 122 ]. Additionally, a previous study reported that DHA regulated nucleocytoplasmic shuttling of lipin-1 to alleviate alcohol-induced liver impairment in mice [ 123 ].…”
Section: Pharmacological Effects Of Artemisinin and Its Derivatives In Vitromentioning
confidence: 99%
“…The antimalarial and antiproliferative drug dihydroartemisinin (DHA), derived from artemisinin, has been reported to function by interacting with free iron in the food vacuole of the malaria parasite, leading to damage of the vacuole through lethal ROS generation (Antoine et al, 2014;Dalal and Klemba, 2015). In addition to antimalarial effects, DHA has been found to also exhibit actions against cancer (Mao et al, 2013;Qin et al, 2015;Zou et al, 2019), inflammatory bowel disease (Yan et al, 2019), alcoholic fatty liver (Chen et al, 2019), osteoarthritic synovium (Li D. et al, 2019), lipopolysaccharide-induced osteoclastogenesis and bone loss (Dou et al, 2016), liver fibrosis (Zhang et al, 2017), and systemic lupus erythematosus . Especially, DHA effectively inhibits cancer cell proliferation in vitro and in vivo (Liao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%